(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
In this work a review of the main empirical studies that have analyzed the abnormal returns obtained by the companies implied in merger or acquisition processes ispresented. Specifically, the main results found in the previous literature are systematized, pointing out the research opportunities that arise associated to the non-conclusiveresults.